2022
DOI: 10.3390/cancers14225480
|View full text |Cite
|
Sign up to set email alerts
|

A GNAS Gene Mutation’s Independent Expression in the Growth of Colorectal Cancer: A Systematic Review and Meta-Analysis

Abstract: Globally, colorectal carcinoma CRC is the third most common cancer and the third most common reason for cancer-associated mortality in both genders. The GNAS mutations are significantly linked with poor prognosis and failed treatment outcomes in CRC. A systematic review and meta-analysis of multiple studies executed following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) criteria and registered with PROSPERO (registration number: CRD42021256452). The initial search includes a tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
(119 reference statements)
0
7
0
Order By: Relevance
“…The 32-gene panel included several genes involved in cancer progression and its putative response to treatment [ 25 , 26 ]. Moreover, our enrichment analysis revealed findings consistent with these 32 genes that were pertinent to the changes in copy number associated with colorectal cancer development and progression [ 23 ], gene mutations important as prognostic biomarkers for colorectal cancer screening and diagnosis [ 26 ], and the upregulation of anti-apoptotic proteins that encourage epithelial–mesenchymal cellular transition (EMT, [ 23 , 25 , 26 , 27 ]).…”
Section: Discussionmentioning
confidence: 96%
“…The 32-gene panel included several genes involved in cancer progression and its putative response to treatment [ 25 , 26 ]. Moreover, our enrichment analysis revealed findings consistent with these 32 genes that were pertinent to the changes in copy number associated with colorectal cancer development and progression [ 23 ], gene mutations important as prognostic biomarkers for colorectal cancer screening and diagnosis [ 26 ], and the upregulation of anti-apoptotic proteins that encourage epithelial–mesenchymal cellular transition (EMT, [ 23 , 25 , 26 , 27 ]).…”
Section: Discussionmentioning
confidence: 96%
“…GNAS (G-protein α subunit), a PKA activator, has frequently been associated with the development of pancreatic cancer [ 31 , 32 ], small cell lung cancer [33] , and colorectal cancer [34] . It has been shown that GNAS can function as a proto-oncogene in solid tumors [35] , while in Sonic hedgehog-driven medulloblastomas, GNAS served as a tumor suppressor [36] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the NGS analysis (Figure 6), GNAS mutation was the only gene alteration correlat-ed with a worse treatment response. A metaanalysis suggested that GNAS mutations are significantly linked with poor prognosis and treatment failure in CRC patients [22]. Survival analyses revealed that patients with KRAS mutations had significantly longer OS1 (P = 0.017), suggesting that the RAS mutation is a predictive marker for better treatment outcomes in patients receiving lenvatinib-based regimens.…”
Section: Discussionmentioning
confidence: 99%